2004
DOI: 10.1016/j.femsec.2004.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Methanol utilization in defined mixed cultures of thermophilic anaerobes in the presence of sulfate

Abstract: We studied thermophilic sulfate reduction with methanol as electron donor in continuous cultures. Mixed cultures of selected microorganisms were used, representing different methanol degrading pathways followed by various trophic groups of microorganisms. Our results show that direct competition for methanol between a homoacetogen, Moorella thermoautotrophica, and a sulfate reducer, Desulfotomaculum kuznetsovii, is in favour of the sulfate reducer due to its affinity for methanol. Methanogenesis as a result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The presence of two methanol-degradation pathways may be beneficial for D. kuznetsovii in its deep-subsurface habitat where it has to compete with other methylotrophic anaerobes. Generally, methanogens and acetogens grow faster with methanol than sulfate reducers, but their growth is hampered by cobalt limitation 35 , 36 , 45 . Methanogens appear to compete better for cobalt during cobalt-limiting conditions 36 , while acetogens outcompete methanogens when the concentrations of methanol and cobalt are high 35 .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of two methanol-degradation pathways may be beneficial for D. kuznetsovii in its deep-subsurface habitat where it has to compete with other methylotrophic anaerobes. Generally, methanogens and acetogens grow faster with methanol than sulfate reducers, but their growth is hampered by cobalt limitation 35 , 36 , 45 . Methanogens appear to compete better for cobalt during cobalt-limiting conditions 36 , while acetogens outcompete methanogens when the concentrations of methanol and cobalt are high 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Butyrate fermentation to acetate, for example, yields only 2H 2 (or 4 eq of H 2 ) per mole of butyrate; therefore, expressed on the basis of expected hydrogen produced from primary fermentation of butyrate, our dose rate of 0.6 mmol/L would have produced only 2.4 meq/L of H 2 -far less than the 12 meq/L of hydrogen added directly to the H 2 -reactor and insufficient, even, to handle the 4 meq/L of PCE added. A similar estimate of H 2 from methanol is not possible since methanol conversion does not necessarily result in a net H 2 production; conversion of methanol to H 2 /CO 2 is only energetically favorable at low hydrogen concentrations and therefore depends on the relative activity of methanol-fermenters and H 2 -users (e.g., dechlorinators, methanogens, sulfate reducers) (Balk et al, 2002;Cord-Ruwish and Ollivier, 1986;Goorissen et al, 2004). In the absence of fast and efficient H 2 -consumption methanol-fermenters will mostly produce acetate instead of H 2 /CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…As also explained in Goorissen, Stams and Hansen in a sulphidogenic process of anaerobic metabolism, methanol could be used as an electron donor for sulphur reducing bacteria or degraded by the combined activity of other microorganisms and changed to carbon dioxide. 16 , 18 The same author also stated that its conversion pathway to carbon dioxide in the presence of sulphate or thiosulphate is energetically more favourable than the production of acetate or methane. The results of the NPOC profile ( Figure 2 ) indicated that increasing growth of biomass increased the NPOC value for the first three days.…”
Section: Discussionmentioning
confidence: 99%